A 3‐D‐printed Luneburg lens antenna with consistent multibeams based on quasi‐pyramid structure. Issue 12 (4th October 2022) - Zang, Yadan; Zhu, Yongzhong; Xie, Wenxuan; Liu, Xiaoyu; Bu, Lijun; Yang, Yufei
Abstract: A wide‐scanning dual‐polarized Luneburg lens antenna based on the quasi‐pyramid structure is proposed. To achieve beam consistency, 18 identical quasi‐pyramid sections are employed to approximate a spherical lens antenna, and each section is divided into 12 layers. The 6‐stepped gradient permittivity index is achieved by the diced ring‐type periodic unit cells in accordance with the Effective Medium Theory. Each quasi‐pyramid is incorporated with the same connecting structure to form an integrity. And a dielectric rod is penetrated parallelly to the center axis of the lens, thus improving the robustness of the overall structure. The radius of the whole lens is merely 0.88 λ 0 . The spherical Luneberg lens antenna is fabricated and measured, with an impedance bandwidth of 45.5%, a measured peak gain of 15.4/15.1 dBi and a cross‐polarization level of higher than 17/17.5 dB. Placing the feed antenna at different locations during the measurement, results attest that those beams possess an excellent consistency. The multibeams are able to achieve an ultra‐wide beam coverage of 165°, promising it a serviceable candidate for mobile communication base stations and wireless networking.